Size matters: an analysis of UK higher education institution mission statements. Issue 3 (3rd May 2020) - Flavin, Michael; Zhou Chen, Ting; Quintero, Valentina
ABSTRACT: Higher Education Institutions (HEIs) have mission statements as a matter of course. This article analyses 127 mission statements from UK HEIs, comprising 76.048% of the mainstream UK higher education sector. The statements were divided into the categories of Russell Group; Other; and Specialist Institution. A mixed methods research approach was adopted. The article identifies the fifty-seven most frequently used terms in mission statements. It also identifies the average lengths for each of the three categories. The article also analyses claims made and language used in mission statements: selected statements were subjected to close analysis. The article shows mission statements from Russell Group universities tend to be shorter, whereas HEIs outside the Russell Group make more detailed statements of their provision and credentials. Structurally, mission statements are distinct between the three categories. Linguistically, there is less distinction, though there is some difference in the most frequently used terms in each category.